Unveiling the structure of unconventional organized crime: Investigating and prosecuting criminal networks within and beyond European borders - Simona Autolitano; Verena Zoppei (Stiftung Wissenschaft und Politik (SWP), 2016)
In the last decades, the traditional understanding of organized crime (OC) has been widely challenged. As the United Nations Office on Drugs and Crime (UNODC), Europol, as well as German authorities have extensively highlighted, hierarchical criminal organizations coexist and overlap with new forms of liquid networked criminality. These criminal networks are composed of flexible alliances between professionals acting worldwide that regulate themselves based on market logic rather than violent conflicts. While appearing "dis-organized," these criminal networks are highly resilient to law enforcement intervention due to their redundancy. Their capacity for infiltrating the legitimate economy and the estimated sums of money they launder globally, which amounts to between 2 and 5 percent of global GDP yearly (UNODC), are alarming. Therefore, not only law enforcement and policymakers, but also the private sector cannot afford to drop their guard. National interventions often just push criminal activities into other countries; hence, effective strategies should address global markets' dynamics. (SWP Comments)
Keywords: 320